The Role of Foreign Direct Investment Towards the Goal of Sustainable Development: Underscoring the Need for A Regulatory Policy Approach in Developing Countries (Dhaka University Law Journal, 2022)
Abstract not availableDhaka University Law Journal, Vol. 32(1), 2021 P.207-230